The Apology of Hattusilis Compared with Other Ancient Dynastic Self-justifications - Wolf, Herbert M. (1967)
Dissertation; contains (1) a detailed analysis from the linguistic and literary critical points of view of the Hittite Apology of Hattusilis, (2) a survey of other documents of self-justification produced by usurpers – Sumerian, Akkadian, Egyptian, West Semitic, and (3) a detailed analysis of I Samuel 15 through II Samuel 8, comparing and contrasting the material from a critical viewpoint with the Apology of Hattusilis; Supervisor: Harry A. Hoffner, Jr. Obtainable through University Microfilms, Ann Arbor, Mich., U.S.A.